Aplicação de Computação em Névoa na Internet das Coisas para Cidades Inteligentes: da Teoria à Prática - Castilho, Gustavo Uruguay; Kamienski, Carlos Alberto (Anais do Workshop em Clouds e Aplicações (WCGA); 2018: Anais do XVI Workshop em Clouds e Aplicações, 2018)
The fog computing concept aims at taking cloud services closer to the clients to optimize resources and increase network performance, since the current centralized model might not be able to handle the demands typical from the Internet of Things. In this paper, we present a generic model for the deployment of fog computing, which can be used as reference for real use cases. We have set up a testbed to demonstrate the feasibility of our model and present results from a performance analysis study that highlights when the use fog computing is viable, based on factors and peculiarities of each use case.